2017
DOI: 10.1108/ijilt-05-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Differences in access to information and communication technologies

Abstract: Purpose Most research on information and communication technologies (ICT) differences has been related to gender and ethnicity, and to a lesser extent religious affiliation. The purpose of this paper is to contribute to this field of research by situating the discussion in the context of British Muslims and extending current research into ICT differences beyond gender and ethnicity. Design/methodology/approach This paper explores the ICT differences in access and use by British Muslim teenage girls at Islami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Instead, their study illustrated that by these initiatives not considering these citizens’ social and cultural contexts as well as diverse literacy needs, these mobile interventions amplified social exclusion rather than mitigated it. Similarly, Hardaker et al’s ( 2017 ) and Tsuria’s ( 2020 ) research demonstrated how religious and gender norms could restrict women’s ability to harness digital technologies despite their ability to access them.…”
Section: The Kaleidoscope Of Theories To Study Digital Inequalitymentioning
confidence: 97%
“…Instead, their study illustrated that by these initiatives not considering these citizens’ social and cultural contexts as well as diverse literacy needs, these mobile interventions amplified social exclusion rather than mitigated it. Similarly, Hardaker et al’s ( 2017 ) and Tsuria’s ( 2020 ) research demonstrated how religious and gender norms could restrict women’s ability to harness digital technologies despite their ability to access them.…”
Section: The Kaleidoscope Of Theories To Study Digital Inequalitymentioning
confidence: 97%